Legal Considerations in the Rebranding Strategy of Menur Mental Hospital: Compliance, Employment, and Data Privacy - Rantetoding, Septevanus (Faculty of Law, Universitas Pekalongan, 2024)
This study examines the legal implications of Menur Mental Hospital's rebranding strategy, with a particular focus on compliance with healthcare regulations, employment law, and data privacy practices. Adopting a quantitative methodology, the research collected data from 200 hospital employees through structured surveys and complemented this with an analysis of internal documents, including compliance policies and privacy protocols, alongside external legal frameworks such as GDPR. Descriptive and inferential statistical methods were applied to evaluate the impact of rebranding on regulatory compliance, employee satisfaction, and data security. The findings indicate substantial improvements in service accessibility, staff engagement, and public perception, coupled with effective management of data privacy concerns. This study highlights the pivotal role of strategic rebranding in addressing systemic challenges in mental healthcare, providing valuable insights for optimizing institutional performance and aligning with public health objectives.